2011
DOI: 10.1111/j.1747-6593.2010.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Hallmarks of organisations that are adapting to climate change

Abstract: This paper explores the question as to 'what do organisations that are adapting to climate change look like?' Examples are drawn from a survey of statutory regulations, guiding principles and organisational documents shaping current practice, with particular emphasis on the water and conservation sectors of industrialised nations. In so far as it is possible to distil recurring themes into common traits, nine hallmarks are identified. These include visionary leadership, objective setting, risk and vulnerabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 23 publications
(18 reference statements)
2
39
0
Order By: Relevance
“…Many of these, however, are specific to particular localities or resources, are not easy to use, and require sophisticated knowledge of climate change (Federspiel 2012;Hammill and Tanner 2011). In general, these approaches seek options that allow reversibility, preserve future options, can resist a variety of impacts, and are flexible, such that mid-course adjustments are possible (OTA 1993;Wilby and Vaughan 2011). Among these approaches are Robust Decision Making (RDM), Iterative Risk Management (IRM), Adaptive Management or CoManagement, Portfolio Management, and Scenario Planning (Gregg et al 2011;Groves and Lempert 2006;Kareiva 2008;Lee 1993;Lempert et al 2006;Moore et al 2012;Moser 2012;NPS 2010;NRC 2004;Williams and Brown 2012).…”
Section: Identifying and Understanding Risk Vulnerabilities And Oppmentioning
confidence: 99%
“…Many of these, however, are specific to particular localities or resources, are not easy to use, and require sophisticated knowledge of climate change (Federspiel 2012;Hammill and Tanner 2011). In general, these approaches seek options that allow reversibility, preserve future options, can resist a variety of impacts, and are flexible, such that mid-course adjustments are possible (OTA 1993;Wilby and Vaughan 2011). Among these approaches are Robust Decision Making (RDM), Iterative Risk Management (IRM), Adaptive Management or CoManagement, Portfolio Management, and Scenario Planning (Gregg et al 2011;Groves and Lempert 2006;Kareiva 2008;Lee 1993;Lempert et al 2006;Moore et al 2012;Moser 2012;NPS 2010;NRC 2004;Williams and Brown 2012).…”
Section: Identifying and Understanding Risk Vulnerabilities And Oppmentioning
confidence: 99%
“…Studies have found that a clear and transparent regulatory environment plays a critical role in encouraging climate change adaptation (CDP, 2012;Wilby and Vaughan, 2011). Governments also have a role to play in encouraging climate change adaptation, by providing credible, accessible scientific information, cofinancing research and development of new products and services, and by forming public-private partnerships to reduce risk (Agrawala et al, 2011;Crawford and Seidel, 2013).…”
Section: Development Of Climate Change Strategies Through Organizatiomentioning
confidence: 96%
“…Despite such investments, evidence suggests those investments have not necessarily translated into the implementation of adaptation policies and measures that reduce vulnerability (Repetto 2008;Schipper and Burton 2009b;Wilby and Vaughan 2011). Rather, a number of authors have noted that an 'adaptation deficit' exists in both developed and developing nations Repetto 2008;Burton 2009a;Moser 2009a).…”
Section: Introductionmentioning
confidence: 94%